2006
DOI: 10.1152/ajplung.00174.2006
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of NPSR1/GPRA in the lung before and after induction of asthma-like disease

Abstract: A genetic contribution to asthma susceptibility is well recognized, and linkage studies have identified a large number of genes associated with asthma pathogenesis. Recently, a locus encoding a seven-transmembrane protein was shown to be associated with asthma in founder populations. The expression of the protein GPRA (G protein-coupled receptor for asthma susceptibility) in human airway epithelia and smooth muscle, and its increased expression in a mouse model of asthma, suggested that a gain-of-function muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
56
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 38 publications
4
56
0
Order By: Relevance
“…Although HGPRT-deficient cells display normal proliferation in vitro (due to unaffected purine de novo synthesis), HGPRT is indispensable in vivo. The level of HPRT1 mRNA was found to be reduced in inflamed lung tissue (Allen et al, 2006). No data have yet been reported on the tissue distribution or metabolism of T-705 in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…Although HGPRT-deficient cells display normal proliferation in vitro (due to unaffected purine de novo synthesis), HGPRT is indispensable in vivo. The level of HPRT1 mRNA was found to be reduced in inflamed lung tissue (Allen et al, 2006). No data have yet been reported on the tissue distribution or metabolism of T-705 in vivo.…”
Section: Discussionmentioning
confidence: 87%
“…For example, Allen and co-workers did not detect expression of GPRA in human lung tissue or in mice with ovalbumin-induced lung inflammation. 10 They also reported that GPRAdeficient mice showed the same allergic airway inflammation responses as the wild-type mice after ovalbumin challenge followed by aerosols of antigen exposure. 10 SNPs in GPRA have been associated with asthma and atopy susceptibility in Caucasians and Asians.…”
Section: Discussionmentioning
confidence: 91%
“…10 They also reported that GPRAdeficient mice showed the same allergic airway inflammation responses as the wild-type mice after ovalbumin challenge followed by aerosols of antigen exposure. 10 SNPs in GPRA have been associated with asthma and atopy susceptibility in Caucasians and Asians. However, findings are inconsistent across populations.…”
Section: Discussionmentioning
confidence: 91%
“…NPSR Ile107 shows a 5-to 10-fold increased agonist sensitivity compared with NPSR Asn107 when measuring second messenger responses, although binding affinity for the natural agonist NPS is unchanged at both receptor isoforms (Reinscheid et al, 2005). This polymorphism had been originally associated with an increased risk of asthma and other allergic diseases (Laitinen et al, 2004), but the role of NPSR in airway function is currently unclear (Allen et al, 2006). We have recently found evidence for a gender-specific association of the NPSR N107I polymorphism with panic disorder , and a genome-wide screen for markers of sleep behavior and circadian phenotypes identified the NPSR Ile107 polymorphism strongly associated with mean bedtime in a random population cohort (Gottlieb et al, 2007).…”
mentioning
confidence: 99%